Strategi Pembelajaran Aqidah Akhlak dalam Membentuk Karakter Anak di Pondok Pesantren Thoriqul Irsyad Gondang Jogoyitnan Wonosobo - Safi'in, Adim; Basit, Abdul (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
The teaching of Aqidah Akhlak in schools plays a vital role in shaping the character and personality of students. At an early age, children are in a formative stage where their thoughts and behaviors can be more easily guided and developed. Therefore, Aqidah Akhlak education is an essential component that must be integrated into the overall learning process, especially within Islamic educational institutions. The values of faith and morality should be embedded in the daily lives of Muslims wherever they are. As future generations, children require a balanced education that includes both general knowledge and religious teachings. An imbalance—particularly an overemphasis on secular subjects—can lead to moral degradation, such as juvenile delinquency, substance abuse, promiscuity, and other forms of misconduct. Hence, the inclusion of Aqidah Akhlak serves as a moral foundation, helping to develop students who possess noble character, exemplary behavior, and strong, principled personalities.